TRADISI BELE KAMPONG PADA MASYARAKAT DESA MENTUDU, KEPULAUAN LINGGA - Mustari, Ozy; Ratnasari, Desi; Apriadi, Robby; Niko, Nikodemus (Master Program in Sociology, Faculty of Social and Political Sciences, Universitas Sriwijay, 2023)
One of the rich and significant cultural practices in the life of the Mentuda Village community is Bele Kampong. The Mentuda people perceive Bele Kampong as a symbol of gratitude, unity, and happiness. The tradition of Bele Kampong holds a profound meaning for the people of Mentuda Village, connecting them to their cultural roots and embodying the values of togetherness, mutual cooperation, and strengthening their relationship with nature. However, this tradition is faced with challenges from modernization and globalization, which can bring about significant changes in social patterns, values, and ways of life within the community. This research aims to deeply understand the social, cultural, and values aspects embedded in the Bele Kampong tradition. Through interviews with traditional elders in Mentuda Village, the researchers explored the community's perceptions and experiences related to this tradition. The research results highlight that the Bele Kampong tradition plays a crucial role in preserving cultural identity, building socio-ecological relationships, and carrying on ancestral heritage. The Mentuda Village community realizes the importance of prudent adaptation without losing the essence of this tradition. Therefore, recommendations for preserving and revitalizing the Bele Kampong tradition include a holistic approach that integrates traditional values with modern elements, as well as educating and raising awareness among the community about the importance of preserving this tradition. This research provides a significant contribution to the efforts to preserve, respect, and strengthen the Bele Kampong tradition as an integral part of the Mentuda Village community's identity, bringing positive impacts on cultural sustainability and social harmony in the future.